Reintroduction of European bison to semi-natural meadows in Grażyna Valley within the confines of the Rural Areas Development Program for years 2007–2013 (European Bison Conservation Newsletter, 2009)
Since the population of European bison Bison bonasus (L.1758) was found on the verge of extinction, the protection of this species has become a matter of particular significance in Poland. The protective activities of European bison mainly focus on captive breeding and free-living herds. The planned introduction of European bison to semi-natural meadows in Grażyna Valley (location: Grabin) is supposed to be an element of active protection of nature in the potential area of Nature 2000, located in rural areas, and to support the restoration of this species in our country. The Program of Rural Areas Development for years 2007–2013, taking into consideration the significant role of grazing animals in shaping the  andscape, encourages and, in some cases, even puts and obligation to farmers to breed the animals in agricultural holdings. At the same time, the program allows for introducing the European bison. The present program allow year-round grazing of only two breeds of little horses. In order to introduce another grazing species; a farmer must submit a request to the Ministry of Agriculture and Rural Development presenting a breeding program and its justification assuring non violation of animals’ welfare. In view of additional formalities and difficulties connected with them, the Committee Monitoring the Program adopted the resolution no. 22/2009 concerning the changes of the Program, which would bring about possibilities of year-round grazing for all grazing species. However, the introduction of European bison to rural areas (areas of permanent meadows and pastures) with the financial support of the Program of Rural Areas Development requires many documents, starting from the permit for the possession of this protected species. Despite this, it is worth using so as to give European bison a chance of living in conditions similar to the natural ones. Therefore, the Institute of Applied Ecology has decided to carry out such a task in order to prove that it is possible to combine the nature and landscape protection with agricultural activity with concurrent financial support of presently available European Union means.
Keywords: reintroduction; financing